International Practica Experiences as Events of Influence in a Teacher Candidates’ Development - Maynes, Nancy; Allison, John; Julien-Schultz, Lynn (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2012)
Experience may influence beliefs and beliefs may influence practices. Following these premises, we investigated teacher candidates’ post experience reflections nine months after an international practicum where they taught for three weeks in rural Kenya. Teacher candidates were placed in non-governmental organization (NGO) sponsored schools on the Maasi Mara southwest of Nairobi. They taught in both elementary (Standard) and secondary (Form) classrooms. Eleven of these candidates responded to a questionnaire with open-ended prompts requiring reflective responses about the perceived impact of their experiences both personally and professionally. Responses were analyzed using qualitative methods to identify common themes and recurring ideas. Examining participants’ responses allowed us to consider how teacher candidates perceived their personal beliefs to impact their personal and professional practices. The significance of the international practica on personal and professional beliefs and practices was evident in responses. Concerns and advantages about the impact of the international experience are explored and directions for further research are identified.